Carnivore abundance near motorways related to prey and roadkills. Issue 2 (2nd November 2017) - Planillo, Aimara; Mata, Cristina; Manica, Andrea; Malo, Juan E.
ABSTRACT: Landscape disturbance by roads may increase abundance of prey in verges (i.e., strips of terrain adjacent to roadways) or create other features that can attract carnivores and expose them to a higher risk of mortality by vehicle collision. We studied a system that included European rabbits ( Oryctolagus cuniculus ) and their predators in central Spain near 3 motorways during 2011 and 2012. We analyzed carnivore and rabbit abundance and the potential effect of prey populations on carnivore roadkill. We estimated rabbit and carnivore abundance index by surveying scats in 1‐km transects in the landscape, and calculated a roadkill index in motorway stretches parallel to the transects from roadkill data obtained in a roadkill monitoring survey from 2007 to 2011. We analyzed carnivore response for the entire carnivore community and for 2 groups of species: the red fox, which is the most synanthropic carnivore in our study area, and the other carnivores. Fox abundance was higher near motorways compared to control sites, whereas the abundance of other species was related only to rabbit abundance. Furthermore, motorway stretches with higher carnivore abundance presented higher values of carnivore roadkills. Thus, motorways are a source of mortality for carnivores that should be managed carefully. The potential cascading effect of food resources near roads on carnivore mortality should be considered in management and food abundance near roads should be minimized in areas inhabited by carnivores of conservation concern. © 2017 The Wildlife Society. Abstract : Red fox, a synanthropic carnivore, selected motorways in the landscape in Spain, whereas non‐synanthropic carnivores responded to prey abundance. When prey densities were high in motorway verges, carnivore densities increased, increasing the number of carnivores killed by vehicles. Minimizing food resources in motorway verges may prevent carnivore mortality from vehicles.